Conhecimento e prática social - a contribuição da sistematização de experiências - Meirelles, Maria Cristina (2007)
The purpose of this work is to ponder on the issue of knowledge production stemming from social practices and particularly from the contributions arising from the systematization of experiences for such a theme. Its goal is to assess and inspect the experiences put forward by persons participating in NGO s (Non-Governmental Organizations) up to the paths that lead to the learning arising from practice to systematization of experiences and to methodologies and knowledge generation. This research initiates from the determination of the current social contexts in which NGO s are inserted, from the establishment of conceptual references useful for such pondering and also from a brief revision of the available literature on systematizing experiences, mainly Latin-American ones. Then six individuals belonging to three NGO s acting nationwide are interviewed. The results show that such lessons stemming from social practices either their own or from other actors have been considered as sources of knowledge by their executive agents. Practical knowledge plays roles on several dimensions of social practice on strenghtening organizational identities, on building references that support social changes, and on permanently shaping the subjects that participate in them, among other things. The ways for building up such knowledge, mutually dissimilar ones, include several assumptions for systematizing experiences, though these do not make up however, within the universe studied, a systematization of experiences exactly as conceived by Latin-American ponderings. On the other hand, the dialogue between the different ways of knowledge production opens up a new set of issues to be dealt with, especially in the education field